Production of Bioethanol and Biodiesel from Water Hyacinth - Kumari, Akriti; Dubey, Sushma (Journal of Neonatal Surgery, 2025)
Biofuels made from biomass are being investigated as a result of the growing need for renewable and sustainable energy sources.The invasive aquatic weed water hyacinth (Eichhornia crassipe, which is distinguished by its high lignocellulosic content and quick growth, offers a biomass that may be used to produce both bioethanol and biodiesel.In order to produce bioethanol and biodiesel from water hyacinth, this study explores a holistic strategy that combines physical, chemical, biological, and enzymatic pretreatment techniques.Prior to fermentation with Saccharomyces cerevisiae to create ethanol, the dried and powdered biomass was subjected to alkali pretreatment and enzymatic hydrolysis with cellulase to liberate fermentable sugars.In order to produce biodiese, lipids were simultaneously removed from the dried biomass using Soxhlet extraction with n-hexane and transesterified using methanol and NaOH.Approximately 8.1 mL of ethanol was produced for every 100 g of biomass, according to experimental results, which showed a glucose yield of 25 g/L.Eight grams of oil were obtained through lipid extraction, and 90% of that was successfully transformed into biodiesel.FTIR, UVVis, and HPLC are examples of analytical methods that verified the successful transformation of biomass into valuable biofuels.The findings underline the feasibility of employing water hyacinth as a costeffective and ecologically acceptable feedstock for integrated bioethanol and biodiesel synthesis, offering a sustainable solution to both energy needs and aquatic weed management.